Against equality : prisons will not protect you - Conrad, Ryan, 1983-; Spade, Dean (Lewiston, ME : Against Equality Pub., 2012)
"Prisons will not protect you critically analyzes the prison industrial complex and the inequality and violence perpetuated by hate crime legislation. This archival anthology provides the history of this legislative panacea and interrogates the gay community's unquestioned loyalty to the prison industrial complex. It argues that hate crime legislation does not address actual causes of harm and violence and, instead, funnels massive numbers of people into the profit-driven prison system"--P. [4] of cover.
Their laws will never make us safer / Dean Spade -- A compilation of critiques on hate crime legislation / Jason Lydon for Black & Pink -- SRLP opposes the Matthew Shepard and James Byrd, Jr. Hate Crimes Prevention Act / Sylvia Rivera Law Project -- Do hate crime laws do any good? / Liliana Segura -- Sanesha Stewart, Lawrence King, and why hate crime legislation won't help / Jack Aponte -- Why hate crime legislation is still not a solution / Yasmin Nair -- Lesbians sentenced for self-defense: all-white jury convicts black women / Imani Keith Henry -- First coffins, now prison? / Sebastien Barraud for PolitiQ-queers solidaires! -- The Devil in Gay, Inc.: how the gay establishment ignored a sex panic fueled by homophobia / James D'Entremont -- "Worst of the worst"? Queer investments in challenging sex offender registries / Erica Meiners, Liam Michaud, Josh Pavan, Bridget Simpson.
Includes bibliographical references.
Keywords: Hate crimes; Gays -- Violence against; Gays -- Crimes against -- United States; Lesbians -- Crimes against -- United States; Gays -- Legal status, laws, etc; Gays -- Legal status, laws, etc -- Statistics; Hatbrott -- Förenta staterna